2022
DOI: 10.1016/j.scs.2021.103560
|View full text |Cite
|
Sign up to set email alerts
|

Modelling energy-efficient renovation adoption and diffusion process for households: A review and a way forward

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…Some scholars have combined the ABM, Game Theory and Regret Theory for technology product diffusion research (Minjie and Zhaoguang, 2011). ABM can also be used to study and compare different development scenarios and evaluate energy policies (Du et al, 2022;Kangur et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…Some scholars have combined the ABM, Game Theory and Regret Theory for technology product diffusion research (Minjie and Zhaoguang, 2011). ABM can also be used to study and compare different development scenarios and evaluate energy policies (Du et al, 2022;Kangur et al, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, there are different views regarding this issue. For instance, Schulte et al [43], Judson and Zirakbash [3], and Du et al [37] identified that small-scale solar microgeneration systems should be considered for the effectiveness of these projects. Furthermore, researchers underlined the importance of other renewable energy alternatives for microgeneration projects, such as small-scale wind turbines [44] and micro hydroelectric powers [45].…”
Section: Discussionmentioning
confidence: 99%
“…This financial gain over time makes energy-efficient construction an attractive option. 11,13 Also, Olopade 14 highlights that cost-effectiveness is closely linked to economic growth and job creation because the adoption of energyefficient construction practices can stimulate economic growth by generating demand for skilled labor and creating opportunities for specialized training programs. 14 The author also stresses that the availability of skilled labor is crucial for implementing energy-efficient systems and technologies, further reinforcing the cost-effectiveness of EEPs.…”
Section: Reviewing Of Existing Literaturementioning
confidence: 99%
“…Practices such as utilizing recycled materials, adopting efficient heating, ventilation, and air conditioning (HVAC) systems and optimizing water management help minimize resource consumption and waste generation. 13 By integrating resource efficiency into EEPs, the construction industry can achieve sustainable and efficient energy practices while reducing their energy demands in buildings. This not only conserves energy resources but also decreases greenhouse gas emissions and the overall carbon footprint of the built environment.…”
Section: Reviewing Of Existing Literaturementioning
confidence: 99%